In Situ Oxygen Isotope Determination in Serpentine Minerals by Ion Microprobe: Reference Materials and Applications to Ultrahigh‐Pressure Serpentinites. Issue 4 (9th July 2018) - Scicchitano, Maria Rosa; Rubatto, Daniela; Hermann, Jörg; Shen, Tingting; Padrón‐Navarta, José Alberto; Williams, Ian S.; Zheng, Yong‐Fei
Abstract : We present the first investigation of in situ oxygen isotopes in serpentine minerals by sensitive high‐resolution ion microprobe (SHRIMP). Chemically homogeneous samples of antigorite (δ 18 O = 8.30 ± 0.12‰), chrysotile (δ 18 O = 4.37 ± 0.02‰) and lizardite (δ 18 O = 5.26 ± 0.20‰) analysed by laser fluorination are identified as potential reference materials. They were analysed by SHRIMP to assess their homogeneity compared with the San Carlos olivine, as well as for potential matrix bias and crystal orientation effects. The reproducibility achieved for all samples was ± 0.30–0.55‰ (95% confidence level). Matrix bias between antigorite/olivine and antigorite/lizardite was up to ~ +3‰ and −1‰, respectively. Crystal orientation effects were identified only in chrysotile, and no matrix bias was observed over the investigated compositional range within each serpentine mineral. The new reference materials were used to measure the oxygen isotope composition of serpentines in an ultrahigh‐pressure metamorphic belt from Tianshan (China). By combining oxygen isotopes and trace element microanalyses, several stages of serpentinisation were recognised: (a) seafloor alteration, (b) recycling of internal metamorphic fluids during isothermal decompression and (c) shallow interaction with meteoric water during exhumation. No interaction with fluids derived from the surrounding metapelites during subduction was identified. Key Points: We developed the first serpentine reference materials for precise and accurate in situ oxygen isotope determination by ion microprobe. Matrix bias effects up to +3‰ and ‐1‰ were observed between antigorite/olivine and antigorite/lizardite. Crystal orientation effects up to 1‰ were observed only in chrysotile.